Dual-Band Bandpass Filter With Controllable Stopband Bandwidth - Wang, Nan; Wei, Haokun; Gao, Kun; Ruan, Xiting; Chen, Xiaojian; Xu, Qian; Yang, Qian; Zhang, Anxue; Liu, Shuangyang (Frontiers in Physics, 2022)
A novel dual-band bandpass filter (BPF) is proposed with independently controllable transmission zeros (TZs) which can realize widely-tunable stopband bandwidth (BW). The planar microstrip filter consists of a three-degree L-C ladder lowpass filter loaded with two unsymmetrical shorted stubs which are used to produce different TZs. By tuning the parameters of the two unsymmetrical shorted stubs, the TZs can be independently controlled. Therefore, the BPF has independent controllable center frequencies (CFs), passband bandwidths, and stopband bandwidths between adjacent passbands. All the L-C values in the equivalent circuit of the proposed filter are optimized to fulfill the design specifications. For demonstration, a dual-band BPF is designed. The measured results show good agreement with the simulated ones.